Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21010/ajtcam.v14i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Citrinin in Grains and Its Possible Health Effects

Abstract: Background: Citrinin is a mycotoxin produced by several species of the genera Aspergillus, Penicillium and Monascus and it occurs mainly in stored grain. Citrinin is generally formed after harvest and occurs mainly in stored grains, it also occurs in other plant products. Often, the co-occurrence with other mycotoxins is observed, especially ochratoxin A, which is usually associated with endemic nephropathy. At the European Union level, systematic monitoring of Citrinin in grains began with the aim of determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…The citrinin toxicity causes primary changes in the kidney characterized by severe degenerative and necrotic changes in the renal tubular epithelial cells causing severe diuresis A prominent finding recorded in the present investigation was membranoproliferative glomerulonephritis wherein the affected glomeruli were swollen, hypercellular and there was eosinophilic homogenous material deposited around the glomerular tufts. Membranoproliferative glomerulonephritis has been reported in broiler chickens associated with IBH and citrinin toxicity [ 30 , 31 ]. Furthermore, neoplasia, autoimmune disorders, and persistent infections due to prolonged viral and bacterial stimulation can cause membranoproliferative glomerulonephritis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The citrinin toxicity causes primary changes in the kidney characterized by severe degenerative and necrotic changes in the renal tubular epithelial cells causing severe diuresis A prominent finding recorded in the present investigation was membranoproliferative glomerulonephritis wherein the affected glomeruli were swollen, hypercellular and there was eosinophilic homogenous material deposited around the glomerular tufts. Membranoproliferative glomerulonephritis has been reported in broiler chickens associated with IBH and citrinin toxicity [ 30 , 31 ]. Furthermore, neoplasia, autoimmune disorders, and persistent infections due to prolonged viral and bacterial stimulation can cause membranoproliferative glomerulonephritis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glomerular lesions occurring in viral infection are mainly due to immune complex deposition [ 30 ]. In citrinin toxicity, inability to filtrate citrinin bound serum proteins and albumin leads to immune complex-induced nephritis [ 31 ]. Apart from citrinin induced nephropathology, citrinin is reported to be a potent immunosuppressive agent due to lymphocytolysis and a potent hepatotoxic agent [ 7 , 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies exist on fungal co-occurrence in maize during the growing season and they are limited to the definition of natural occurrence of different mycotoxins in maize without considering fungal presence and/or interactions under in field conditions (Kovalsky et al, 2016; Culig et al, 2017; Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent animal experiments have shown that CIT has nephrotoxicity [5], hepatotoxicity, teratogenicity, carcinogenesis, and other negative effects on animal health, and CIT is therefore listed as a mycotoxin. The contamination of CIT is widespread and can occur in cereal agricultural products [6] and animal feed, such as wheat [7], barley [8], corn [9], rice [10,11], and cereal products [12]. In addition, its main producing strain, Monascus, produces a large amount of CIT during fermentation [13,14].…”
Section: Introductionmentioning
confidence: 99%